IMPLEMENTASI PASAL 9 PERATURAN DAERAH KOTA PEKANBARU NOMOR 12 TAHUN 2008 TENTANG KETERTIBAN SOSIAL DALAM PEMBINAAN GELANDANGAN DAN PENGEMIS - Aditia Herman; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The city of Pekanbaru does not yet have a Social Home as a HomelessRehabilitation Site and Beggars only have a Shelter House. This shelter is atemporary place and is intended as a place of residence for recipients of servicesprepared to obtain further services. At this halfway house only have rehabilitationin the form of mental counseling and religious counseling, without the provisionof skills. Non-governmental organizations (NGOs) that work with the SocialService only handle neglected children. And while entrepreneurs only providesocial assistance. In its implementation, Regional Regulation Number 12 of 2008concerning Social Order has not been implemented optimallyThis type of research can be classified as a sociological jurid, namely aresearch approach that emphasizes the legal aspects relating to the subject matterto be discussed, related to the reality in the field. This research was conducted atthe Pekanbaru City Civil Service Police Unit and the Pekanbaru City SocialService, while the sample population was all parties related to the problem understudy. Data sources used, primary data and secondary data and tertiary data,data collection techniques in this study with questionnaires, interviews andliterature studies.In the results of the problem research there are three main things thatcan be concluded. First, the implementation of Regional Regulation Number 12 of2008 concerning Social Order does not work as it should. Second, the inhibitingfactor in the implementation of these Regional Regulations is the limited budget,limited human resources, lack of facilities and infrastructure and implementationof regional regulations are not working. quality of human resources and completeexisting facilities and infrastructure.key words: Implementation, Rehabilitation, Homelessness and Beggars